160k views
3 votes
Hi. I need help with this questions.
See image for question



Hi. I need help with this questions. See image for question ​-example-1

1 Answer

4 votes

Answer:

  • None

Explanation:

Given expression

  • 9x² - 2(k + 7)x + k

If this is a perfect square then it should be in the form of:

  • (3x)² - 2(3x)(√k) + (√k)²

Comparing the two expressions, we see that:

  • (k + 7) = 3√k
  • (k + 7)² = 9k
  • k² + 14k + 49 - 9k = 0
  • k² + 5k + 49 = 0
  • D = √(5² -4*49) = √-171

Since the discriminant is negative, there is no solution

User Chester
by
4.6k points